KASHMIRI PANDITS AND THEIR EXODUS - Jha, Pratiksha; Verma , Mukul Bihari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The plight of Kashmiri Pandits have been receiving more attention in recent years. In this Paper the forceful displacement and persecution of Kashmiri Pandits will be discuss. The Pandits have been forcefully displaced from their own motherland since 13th century and their last exodus took place after 1990 under the nose of a democratic elected government. Their displacement was earlier overlooked by the government as Kashmiri Pandits themselves claimed. The displacement of Kashmiri Pandits not only impacted the Indian Political system but it also impacted the plural, federal characteristic of the Indian constitution and Indian society. So in this paper we will discuss how when and under what circumstances Kashmiri Pandits had to leave their motherland.